2015
DOI: 10.1186/s13054-015-1067-6
|View full text |Cite
|
Sign up to set email alerts
|

Associations of arterial carbon dioxide and arterial oxygen concentrations with hospital mortality after resuscitation from cardiac arrest

Abstract: IntroductionArterial concentrations of carbon dioxide (PaCO2) and oxygen (PaO2) during admission to the intensive care unit (ICU) may substantially affect organ perfusion and outcome after cardiac arrest. Our aim was to investigate the independent and synergistic effects of both parameters on hospital mortality.MethodsThis was a cohort study using data from mechanically ventilated cardiac arrest patients in the Dutch National Intensive Care Evaluation (NICE) registry between 2007 and 2012. PaCO2 and PaO2 level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 40 publications
6
82
0
5
Order By: Relevance
“…Among 12,108 ICU patients in New Zealand, Bellomo, et al observed associations between hyperoxemia and hospital mortality, but these relatioships were not as strong on sensitivity analyses [10]. In a study of 5258 cardiac arrest patients admitted to 82 ICUs in the Netherlands, Helmermorst et al observed increased hospital mortality from all oxygen and carbon dioxide aberrancies [12]. Among 409 patients admitted to 21 ICUs in Finland, Vaahersalo, et al found no association between oxygen and carbon dioxide tensions and 12-month neurologic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Among 12,108 ICU patients in New Zealand, Bellomo, et al observed associations between hyperoxemia and hospital mortality, but these relatioships were not as strong on sensitivity analyses [10]. In a study of 5258 cardiac arrest patients admitted to 82 ICUs in the Netherlands, Helmermorst et al observed increased hospital mortality from all oxygen and carbon dioxide aberrancies [12]. Among 409 patients admitted to 21 ICUs in Finland, Vaahersalo, et al found no association between oxygen and carbon dioxide tensions and 12-month neurologic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity rose more rapidly as FiO 2 is increased above 0.6 and also as exposure time is prolonged (4,18,37,38). Available data showed a U-shaped relationship between mortality and arterial PaO 2 (52). Mortality sharply increased at PaO 2 <65 and >225 mmHg (1).…”
Section: Conservative O 2 Strategymentioning
confidence: 98%
“…Early oxygen administration can influence oxidative metabolism, respiratory markers, vasoconstrictive status and blood flow, and may thus be an important predictor of outcome [20]. Although it is intuitive that insufficient oxygen delivery can exacerbate cerebral anoxia, excessive oxygen delivery can also be harmful by increasing the amount of oxygen free radicals and subsequent reperfusion injury.…”
Section: Normoxia and Normocapniamentioning
confidence: 99%
“…Although it is intuitive that insufficient oxygen delivery can exacerbate cerebral anoxia, excessive oxygen delivery can also be harmful by increasing the amount of oxygen free radicals and subsequent reperfusion injury. Pure oxygen therapy after cardiac arrest has previously been shown to worsen neurological outcome in animal models and exposure to hypocapnia and hypercapnia after ROSC has been associated with poor neurological function at hospital discharge [20].…”
Section: Normoxia and Normocapniamentioning
confidence: 99%